Herb Schildt's C++ Programming Cookbook - Schildt, Herbert (McGraw-Hill Companies., 2011)
This book is a collection of techniques that show how to perform various programming tasks in C++. As the title implies, it uses the well-known "cookbook" format. Each "recipe" illustrates how to accomplish a specific operation. For example, there are recipes that read bytes from a file, reverse a string, sort the contents of a container, format numeric data, and so on. In the same way that a recipe in a food cookbook describes a set of ingredients and a sequence of instructions necessary to prepare a dish, each technique in this book describes a set of key program elements and the sequence of steps necessary to use them to accomplish a programming task. Ultimately, the goal of this book is to save you time and effort during program development. Many programming tasks consist of a set of standard functions and classes, which must be applied in a specific sequence. The trouble is that sometimes you don't know which functions to use or what classes are appropriate. Instead of having to wade through reams of documentation and online tutorials to determine how to approach some task, you can look up its recipe. Each recipe shows one way to craft a solution, describing the necessary elements and the order in which they must be used. With this information, you can design a solution that fits your specific need.